Quranic concept of war - "Malik, S. K." (New Delhi, 1986)
In this book the Quranic philosophy of war has been analysed from a technical and professional point of view. The book begins with a description of the historical, political as well as Quranic perspective to the formation of the Muslim Ummah.
Keywords: War Religious aspects